Diagnóstico situacional para identificar los Problemas Turísticos en el cantón Sigchos - Pastuña Nogales, Nataly Jimena (2020)
The research project had the purpose to determine tourist problems at Sigchos canton, allowing to identify direct beneficiaries, such as providers of tourist services and indirect beneficiaries, all the inhabitants of the canton. For data collecting to the first objective, the land use plans for the years 2012-2020 and 2015-2065 were used, as well as an unstructured interview with legal representative of Tourism Association Community, as a result of the first objective was to find the geographical distribution, the ethnic groups present in the canton are indigenous, mestizos and montubios that are found in its 5 parishes, in the same way the canton has a minimum temperature of 2ºC and its maximum of 20 ºC, due to wheatear, and can be found a variety of native flora and fauna, at the same time it has a variety of natural and cultural attractions. It is worth mentioning that its main source is agriculture and livestock. For the second objective, a matrix was made with the list of problems that correspond to tourism system elements; superstructure, infrastructure and structure and the relationship with the political, economic, sociocultural, technological, legal and environmental spheres, determining 29 problems that directly affect tourism development and a rating of; 3 high, 2 medium and 1 low, depending by impact degree that they cause, in the high impact problems identified, strategies were developed to mitigate them. The identified problems in the superstructure are the changes of governments and the lack of proposals for improvement related to tourism sector, in turn, the parish councils do not designate an appropriate budget for them, the canton has a diversity of tourist attractions, but it does not have projects that promote their progress or do not comply with the environmental protection laws issued by the MAE. In the infrastructure, tourism service providers work without the respective permits, Sigchos does not have the adequate tourist plant, the telecommunications system and electrical energy are in a regular state and contamination by solid and liquid waste is an environmental problem of high impact in the canton. In the structure, the lack of signage in the attractions as well as forest fires and the felling of trees without the respective permits, the way to carry out tourist activities in an empirical way since they do not have local guides and leisure and recreation spaces. they are not delimited. The project carried out contributes in a very significant way since the problems that affect tourism, strategies were developed that should begin to be applied, the most essential strategy is joint work the GAD cantonal with different parish GAD's, and communities where generated projects to development the communities and the canton in the tourism field.